Calorie Deprivation in Rural India, 1983-1999/2000 - Viswanathan, Brinda; Meenakshi, J.V. (Economic and Political Weekly, 2003)
Income poverty has declined over the 1980s and 1990s, but so have calorie intakes so that calorie deprivation in rural India has in fact increased. However, the depth and severity of nutrient deprivation declined, as did the incidence of abject calorie deprivation. Crucially, the results are sensitive to the choice of both calorie norm and poverty measure. The apparent divergence between income- and calorie- poverty trends further underscores the need for fresh debate on the determination both of the calorie norm and the poverty line.
Keywords: Calorie Deprivation; India; Poverty; Rural India